Perancangan Interior Rumah Pernikahan Pada LKP Lelly Dengan Konsep Personal White - Juli Atika; Rani Hermita; Muslida Murti (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Referring to the modern lifestyle, to carry out a wedding, there are many needs that must be prepared, so it takes a lot of time and costs quite a lot. Many vendors provide party needs, but do not provide all needs in one area. So that the bride and groom need more time, energy and money to go to different places to meet all the needs of the party, the interior design of this Wedding House adopts a concept with the title